Optimization of the Utilization of the Rumah Pendidikan Platform in Teacher Career Development within MGMP Groups - Lestari, Fifi Undariani; Maya Novita Sari (RUBINSTEIN, 2026)
Digital transformation in education, marked by the launch of the Rumah Pendidikan Platform by the Ministry of Primary and Secondary Education in January 2025, has created new opportunities for independent and integrated teacher career development. This study aims to analyze the optimization of the platform’s use in supporting teacher career development, identify the obstacles encountered, and formulate optimization strategies within the Mathematics MGMP of Regional Coordinator III, Bengkalis Regency. The study employs a descriptive qualitative approach, with data collected through in-depth interviews, observation, and documentation. Research subjects were selected using purposive sampling and included the MGMP chairperson, active teacher members, and school principals. Data analysis followed an interactive model, while source, technique, and time triangulation were applied to ensure data validity. The findings show that the platform contributes significantly to improving teachers’ pedagogical competence through independent training modules and supports the fulfillment of promotion credit points through digital documentation of certificates and academic works. MGMP plays a strategic role as a collaborative ecosystem that accelerates platform adoption through digital literacy programs and a buddy system. However, three main challenges were identified: limited internet infrastructure, heavy administrative workloads, and non-mandatory regional policies.